Óleos essenciais emulsionados e nanoemulsionados no controle de C. botulinum e C. sporogenes em mortadela - Pinelli, Juliana Junqueira (2022)
The growing demand by consumers for natural products has intensified in recent years, causing the food industry to invest more and more in the research and development of natural preservatives that can be applied to food without posing risks to human health and that have the same functions as synthetic preservatives. In this scenario, essential oils obtained from plants stand out, since they have already proven antimicrobial and antioxidant action and their application in foods is considered safe (GRAS). Although essential oils have antimicrobial activity against several microorganisms, their application in foods is restricted, mainly due to their low water solubility, their unwanted sensory effects and interactions with food constituents that make their action difficult. Thus, new ways of applying these oils in food have been studied, such as the use of essential oil nanoemulsions, which seeks to make these compounds more reactive, but with lesser effects on the sensory properties of the product. The objective of this work was to evaluate the antimicrobial activity of the combination of essential oils of garlic, clove, pink pepper and black pepper, and their respective nanoemulsion, in the control of endospores of Clostridium botulinum and Clostridium sporogenes inoculated in mortadella, as well as their influence on technological (pH, water activity and color) and sensory characteristics of the product. The combination of oils tested, as well as its nanoemulsion, showed satisfactory effects on the endospores of both microorganisms tested. However, regarding the technological and sensorial characteristics of the product, the addition of combined essential oils, both emulsified and nanoemulsified, had a strong impact on the color of the mortadella and on the flavor/aroma, indicating the need for further studies to minimize these changes.